2013
DOI: 10.1017/s1742170513000343
|View full text |Cite
|
Sign up to set email alerts
|

Response to farmer mass selection in early generation progeny of bread wheat landrace crosses

Abstract: A participatory plant breeding (PPB) program involving the French farmers' association 'Réseau Semences Paysannes' and the French National Agricultural Research Institute (INRA) at Le Moulon was initiated in 2005. In the process of designing the breeding scheme, we evaluated the impact of farmer selection at an early stage (F 2 ) on bread wheat cross progeny populations. The objectives were to characterize the effect of farmer selection, to evaluate the impact of farmer selection on intra-varietal diversity, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…Several studies have demonstrated that the highest breeding gain for OA could only be achieved when selecting under the target conditions of organic farming [64,84]. This either requires breeding companies to include organic selection fields in the program [85] or involve organic farmers in the selection process [86]. Besides, the potential of within-crop diversity, such as composite cross populations in cereals and mixtures of modern cultivars [87], and breeding for mixed cropping systems [88] are being explored to enhance yield stability and the resilience of organic agro-systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the highest breeding gain for OA could only be achieved when selecting under the target conditions of organic farming [64,84]. This either requires breeding companies to include organic selection fields in the program [85] or involve organic farmers in the selection process [86]. Besides, the potential of within-crop diversity, such as composite cross populations in cereals and mixtures of modern cultivars [87], and breeding for mixed cropping systems [88] are being explored to enhance yield stability and the resilience of organic agro-systems.…”
Section: Discussionmentioning
confidence: 99%
“…Such can be powerful and cost efficient approaches for developing a diverse assortment of locally adapted and open pollinated cultivars for a large range of crops [86,89,90], with the possibility to achieve equal or higher yield compared to modern high yielding F1 hybrids due to optimized use of local/regional adaptation [91]. An example is the case of open pollinated sweet corn development in USA [92].…”
Section: Discussionmentioning
confidence: 99%
“…Il en appréciait certaines qualités (valeur boulangère, pailles hautes utiles à l'agriculture biologique), mais regrettait dans le même temps l'expression (accrue dans les conditions modernes de culture) d'un défaut majeur, la sensibilité à la verse. Il décide alors de faire des croisements afin de réunir les qualités et intérêts complémentaires des unes et des autres Rivière et al, 2013Rivière et al, , 2015b. À sa demande, l'équipe « Diversité, évolution et adaptation des populations » (DEAP) de l'INRA (UMR GQE [Génétique quantitative et évolution], Le Moulon) vient l'aider à faire plus de 90 croisements.…”
Section: S56unclassified
“…This project has contributed to the selection and subsequent market success of several new pepper varieties (Waterbury, 2013), demonstrating how engaging the culinary community in the selection process can facilitate rapid adoption of new varieties. Rivière et al (2015) describe a participatory breeding program in France that worked to improve productivity of organic bread wheat. In this project, the original parental variety selections were made by a farmer-baker and hybridizations of these parental varieties were performed on-farm.…”
Section: Model 3 Farmer-based End-use Selection: Development Of Folkmentioning
confidence: 99%